Temporal Discounting for Multidimensional Economic Agents - BOTA, Florentin (Studia Universitatis Babeș-Bolyai Informatica, 2021)
Individuals frequently place a higher value on money and goods today than they would in the future. This is known as temporal or time discounting, and most economic models include discount functions to represent such utility over time. In this paper we evaluated traditional models with experimental data from the scientific literature and constructed our own samples for comparison. In addition, we evaluated the prediction accuracy of the models and proposed new hybrid solutions. Our investigation aims to contribute to a better understanding of human nature in complex processes. Received by the editors: 3 April 2021. 2010 Mathematics Subject Classification. 68Q19, 91B44. 1998 CR Categories and Descriptors. J.4 [Computer Applications]: Social and BehavioralSciences – Economics; I.6.4 [Computing Methodologies]: Simulation and Modeling – Model Validation and Analysis.